2015
DOI: 10.2106/jbjs.m.00235
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up After Latissimus Dorsi Transfer for Irreparable Posterosuperior Rotator Cuff Tears

Abstract: Pain relief and improvement of shoulder function were maintained a mean of 9.3 years after latissimus dorsi transfer for irreparable posterosuperior cuff defects. The younger the patient, the better the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
1
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 36 publications
11
117
1
24
Order By: Relevance
“…121 Clinical outcomes Studies regarding the clinical outcomes of latissimus dorsi tendon transfers are summarized in Supplementary Table III. 3,15,20,23,26,29,41,[43][44][45]61,62,75,89,92,98,116,121,122 A systematic review conducted by Namdari et al analyzed 10 studies between 1992 and 2010 to determine the expected outcomes, predictive factors for success, and complications of latissimus dorsi transfers. 94 Frequency-weighted mean follow-up was 45.5 months.…”
Section: Tendon Transfersmentioning
confidence: 99%
“…121 Clinical outcomes Studies regarding the clinical outcomes of latissimus dorsi tendon transfers are summarized in Supplementary Table III. 3,15,20,23,26,29,41,[43][44][45]61,62,75,89,92,98,116,121,122 A systematic review conducted by Namdari et al analyzed 10 studies between 1992 and 2010 to determine the expected outcomes, predictive factors for success, and complications of latissimus dorsi transfers. 94 Frequency-weighted mean follow-up was 45.5 months.…”
Section: Tendon Transfersmentioning
confidence: 99%
“…Patient satisfaction following operation remains high [32, 43-45, 47, 81, 112], while a high percentage of patients has been reported to be willing to undergo the operation again [42, 78, 84]. Operative outcomes have been demonstrated to be sustained in the long term, preserving pain relief and range of motion [55, 127]. There are some reports however, demonstrating deterioration of results with time and reemergence of pain [24, 27].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that radiologic findings regarding arthritic degeneration are not related to the clinical outcomes [43, 54, 117]. Nevertheless joint degeneration is anticipated [43, 75, 117] due to degradation of the tenodesis effect over time [131], a finding evident in several studies that demonstrated a decrease in acromiohumeral distance in the mid [130] and long term [55, 127] in comparison to the initial postoperative outcome. It has been suggested however, that potentially LD tendon transfer may prolong the time till arthroplasty [131].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,14,15] Outcomes of this procedure is widely studied till date. [8,15,16,17] The major concern about this procedure was deltoid damage which was dramatically reduced by adapting arthroscopic assisted LDT, since it has been found in one study that once injured deltoid fails to recuperate its normal power. [14] Although only a handful of studies have evaluated outcomes of arthroscopic LDTT, findings of these studies are more than satisfying especially in terms of absence of occurrence of glenohumeral arthritis and absence of diminution of subacromial space.…”
Section: Introductionmentioning
confidence: 99%